Elliptical Sentence In Open File A Cliff Hardy Novel by Peter Corris - Pertiwi, Putu Mesia; Putra, I Gusti Bagus Wahyu Nugraha; Winarta, I. B Gde Nova (Lingual Journal of Language and Culture, 2021)
Ellipsis is a branch of syntax that study about elimination word to avoid repetition word in the sentence. This study concern to find out the types of elliptical sentence and analyze the constituent structure of sentence in the novel by Peter Corris in title Open File A Cliff Hardy. This study applied the theory proposed by Quirk and Greenbaum (1973) to find out the types of elliptical sentence and the theory from Brown and Miller (1991) to analyze the constituent structure of sentence. The data were collected by documentation method and analyzed descriptively by qualitative method. The finding shows that there are five types of elliptical sentence which the most dominant is ellipsis of subject (and auxiliary)